O lápis endiabrado: adrelino cotta e a caricatura em Belém do Pará nos anos 20 - CASTRO, Raimundo Nonato de (Universidade Federal do Pará, 2019)
The city of Belém in the 1920s carried in the imagination of its population the idea that the urbs was marked by its “modern” aspects. And the ideal stage to reinforce this imaginary was the pages of the periodicals and weeklies that circulated in the capital of Pará in the first decades of the twentieth century. It is precisely in this context that the figure of Andrelino Cotta was able to construct, through his analyzes, images that were able to question how “modern” Belém was seen in the notice of the various problems experienced in the capital of Pará. With the caricature representations, for example, the periodicals had the guns capable of conducting the interpretations in the process of symbolic formation, creating stereotypes, which look for represent the city. In newspapers and magazines, they constructed representations of the most diverse, such as those of humorous character that were marked by the brief, concise, truncated, fast and reversed aspects of meanings, demonstrating a certain familiarity. In this aspect of ideological dispute, the intellectuals were active in the editorial circuit, in special, the comedians stood out for construct by pencil the artistic production filled with double interpretation.